Religiosidade e saúde mental em um CAPS de Belém do Pará: cenas de um enredo cultural - Araújo, Lucivaldo da Silva (2015)
Belém of Pará stands out in the Brazilian religious scenario, among other things, for sheltering the largest at present Catholic procession - the Círio of Nazareth; besides being the birthplace of the largest Pentecostal evangelical church in the world - the Assembly of God. Such peculiarities, together with the cultural and religious influence of European, African and indigenous, and religious involvement of institutions and professionals in the care services for mental health, motivated the realization of this qualitative research of phenomenological orientation, in order to understand how happen the unique relationship between religiosity and mental health in a Psychosocial Care Center (CAPS) in Belém of Pará. The participant observation, the experience of Círio of Nazareth and the realization of eleven interviews with professionals enabled us to access the space of care permeated by various components of the religious cultural identity the people of Pará. In CAPS, prayers, hymns, Bible reading, spiritualists impositions of hands, mantras, mentalizations and etc., appears with religious and therapeutic purposes, that is, are developed to improve the clinical symptoms of patients. It is a clinic culturally instituted by people whose ethos of water allows them to take on multiple forms. Net practice, indefinite and without edges, which develops into a place where "men and gods walk together." This particular and transgression mode of mental health highlights the limits of the own clinic. Reveals a process that is organized and shown effective in its own terms, and thus appears as a possibility front of insufficient theories which do not deal with the complexity of human problems